Case report: Incidence and prognostic value of brain MRI lesions and elevated cerebrospinal fluid protein in children with Guillain-Barré syndrome - Pizzo, Francesco; Di Nora, Alessandra; Di Mari, Alessia; Costanza, Giuseppe; Testa, Elisabetta; Strazzieri, Marianna; Greco, Filippo; Timpanaro, Tiziana; Basile, Antonio; Belfiore, Giuseppe; Giugno, Andrea; Rocca, Roberta; et al. (Frontiers in Neurology, 2022)
background: Guillain-Barrè syndrome (GBS) is an acute immune-mediated disorder affecting peripheral nerves and nerve roots with a variable clinical course and outcome. Epidemiologic analyses have revealed the incidence of the syndrome increases linearly among the age. The clinical diagnosis of GBS is based on the family history, physical and neurological examination, electrodiagnostic exams, and cerebrospinal fluid analysis with the classical presence of albumin-cytologic dissociation. Prognosis is associated with the severity of clinical signs and the type of peripheral nerves involved. Methods: The aim of this study, was to clear clinical features to be used for a prognostic purpose. We evaluated the correlation between 1) Brain MRI lesions and grade of disability; 2) Brain MRI lesions and elevated cerebrospinal fluid (CSF) protein; 3) elevated CSF protein and grade of disability. Statistical analysis extracted from these data indicated a good correlation to be a prognostic indicator in children affected by GBS. We found little evidence regarding laboratory tests, imaging, and prognosis. We enrolled 12 continuous patients who met the Brighton criteria for GBS in this retrospective study. Each patient was clinically evaluated at the time of disease onset assessing the GBS disability score and after 2 weeks. Results: We estimated Pearson's correlation index to evaluate the possible correlation between MRI and Disability and CSF Protein Levels and Disability. The correlation coefficient was respectively 0.92 and 0.85. We also developed a graph to see the trend of the disability values, proteins in the CSF, and damage assessed with MRI in the 12 patients. It seems that these parameters have a parallel trend and a good correlation in each patient. Finally, we calculated the correlation between MRI and CSF protein values, r-value of 0.87. The values suggest a correlation between the MRI score, CSF protein, and prognosis. Conclusions: Patients who need ventilatory support could be established early from patients who have less severe GBS and can begin rehabilitation earlier. We suggest MRI should be performed routinely in children with GBS to be able to estimate the evolution of the clinical condition.